Theoretical foundations of the "Geary Method" for international comparisons of purchasing power and real incomes - Neary, J. Peter (Economic & Social Studies, 1996)
This paper provides a centenary review of the method of calculating real incomes and purchasing power parities proposed by Roy Geary. This method is the most widely used in major international comparisons, but it is often criticised for its lack of theoretical foundations. I discuss the properties of the method and its competitors in the light of both practical and theoretical considerations. I also propose a new method of computing "true" or, as I call them, "Geary-Konus" exchange rates and world prices and I argue that the Geary method provides the best available approximation to the true values.
Keywords: Roy Geary; real incomes; statistical methods